MORAL FACTORS THAT ENCOURAGE THE MAIN CHARACTER TO ACHIEVE SELF UNITY IN THE NOVEL "BEAUTY AND THE BEAST" BY ELIZABETH RUDNICK - Desica Desica; Tomi Arianto (eScience Humanity Journal, 2022)
This study aimed to explore the moral factors that encourage the main character to achieve self-unity in the novel “Beauty and the Beast by Elizabeth Rudnick. This study used a philosophical approach related to exploring the elements of morality in literary works. The theory used is the theory of Linda and Richard (1993) about the form of moral values, and Cady's theory (2005) about the influential factors in moral formation. The research method used in this research is descriptive qualitative. Then, the researcher applied the library research method. The moral principles of the main character are portrayed in the attributes of honesty, courage, peace, independence and potential, discipline and moderation, respect, love, selflessness and sensitivity, kindness and friendliness, justice and compassion, according to the findings of this study. Meanwhile, the variables that lead to the creation of moral values might come from chance, intents from the environment, and their own will. Except for the principles of loyalty and chastity, Belle, the novel's main character, has demonstrated all of the moral values that have been theorized. Belle is most influenced by her own willingness to demonstrate her moral principles, which is caused by various factors that influence her to practice such beliefs, according to the investigation.